2005
DOI: 10.1614/ws-05-064r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting seed persistence of annual weeds across the U.S. corn belt

Abstract: Weed seedbanks have been studied intensively at local scales, but to date, there have been no regional-scale studies of weed seedbank persistence. Empirical and modeling studies indicate that reducing weed seedbank persistence can play an important role in integrated weed management. Annual seedbank persistence of 13 summer annual weed species was studied from 2001 through 2003 at eight locations in the north central United States and one location in the northwestern United States. Effects of seed depth placem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 25 publications
11
79
2
Order By: Relevance
“…The black soil, which was the warmest and wettest, aged seeds of all three species more quickly than the cooler and drier red and sandy soils. These results are supported by other field studies that found higher soil water and temperature conditions to increase seed mortality (Davis et al 2005;Mickelson and Grey 2006;Van et al 2005). Indeed, raising temperature and water content reduces seed longevity in ex situ storage (Walters 1998).…”
Section: Discussionsupporting
confidence: 85%
“…The black soil, which was the warmest and wettest, aged seeds of all three species more quickly than the cooler and drier red and sandy soils. These results are supported by other field studies that found higher soil water and temperature conditions to increase seed mortality (Davis et al 2005;Mickelson and Grey 2006;Van et al 2005). Indeed, raising temperature and water content reduces seed longevity in ex situ storage (Walters 1998).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, site was often a more important predictor variable than crop habitat or the interaction between site and crop habitat. This result is congruent with many previous studies that have successfully used site as a predictor of plant distribution and performance (Byers and Quinn 1998;Davis et al 2005;Joshi et al 2001;Santamaria et al 2003). Because the climatic and environmental properties associated with individual locations are abundant, unique, and often highly correlated, site may be the most effective predictor of plant distribution (Andreasen et al 1991;Byers and Quinn 1998;Dale et al 1992).…”
Section: Effect Demographic Parametersupporting
confidence: 89%
“…Similarly, the year{site} effect explained 66, 63, 64, and 51% of the variation in Sw, Ss, G, and SSDL for HELAN, respectively (Figure 4). The large amount of variation explained by the year{site} effect for these demographic parameters for both species indicates the importance of environmental factors that conditioned each site-year (e.g., crop management, precipitation, soil moisture, and temperature; Davis et al 2005).…”
Section: --------------------------------------------------------P-vamentioning
confidence: 99%
“…Weber ex Wiggers (dandelion), and Chenopodium album L. (common lambsquarters). These species are commonly found in the Northeastern United States [40,41], but also throughout Europe [2] in summer-sown crops [42]. For the entire dataset, 61 of the 106 species recorded had a frequency of occurrence greater than 2% (i.e., more than 4 occurrences) and only 38 species had a frequency of greater than 5% (i.e., more than 10 occurrences).…”
Section: Weed Communities and Ecological Gradientsmentioning
confidence: 99%